Micro-RNA149 confers taxane resistance to malignant mesothelioma cells via regulation of P-glycoprotein expression. Issue 3 (4th March 2018) - Kenworthy, Rachael; Bosco, Dale B.; DeLigio, James T.; Zorio, Diego A. R.
ABSTRACT: Multidrug resistance (MDR) represents a major hindrance to the efficacy of cancer chemotherapeutics. While surgical resection, radiation, and chemotherapy can be used to reduce tumor size, the subsequent appearance of drug resistant cells is a frequent problem. One of the main contributors to the development of MDR is increased expression of multi-drug resistant protein 1 (MDR1), also known as P-glycoprotein (P-gp). P-gp is a membrane-associated efflux pump that can efficiently remove internalized taxane-base chemotherapeutics thus preventing drug accumulation and maintaining cellular viability. Consequently, investigation into the molecular mechanisms responsible for regulation of P-gp expression is necessary to facilitate treatment of MDR tumors. Using molecular and biochemical approaches, we identified that the micro-RNA, miRNA149, contributes to the development of MDR within malignant mesothelioma cells by regulating the expression of MDR1.